SUPPLY CHAIN MANAGEMENT AND CUSTOMER SATISFACTION: EVIDENCE FROM TWO LUXURY 3-STAR RATED HOTELS IN THE BONO REGION OF GHANA - Ayam, J. R. A.; Kusi, S. (UDS International Journal of Development, 2023)
The hospitability industry continues to face mounting pressures and demand for increased customer satisfaction by customers. The increased relevance of Supply chain management (SCM) influence on services rendered by the industry and the ripple effect on the satisfaction of customers of businesses in the value chain has been well articulated. This study examines the influence of SCM practices on customer satisfaction in two 3-Star rated hotels in the Bono Region of Ghana. Quantitative survey research methodology was adopted with data collected from a sample of 32 employees and 92 customers of the selected study hotels in the Bono Region of Ghana using a structured survey questionnaire. The outcome identified three SCM factors namely: strategic supplier partnership, inventory management and lean practices which showed significant relationship in determining customer satisfaction in the 3-Star hotel cohorts under study in the region. The results also showed an overall positive significant relationship between SCM factors and customer satisfaction in the facilities studied. The factors, thus: strategic supplier partnership, inventory management and lean practices were found to be significant in predicting best fit equation for customer satisfaction. The study recommended that practitioners should maintain accurate databases of suppliers to facilitate effective information sharing and routine training of their employees. Keywords: Supply Chain Management, Customer Satisfaction, 3-Star Hotels, Hospitality Industry, Ghana